2016
DOI: 10.1186/s13059-016-1111-0
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal genetic control of human gene expression does not differ across the sexes

Abstract: BackgroundDespite their nearly identical genomes, males and females differ in risk, incidence, prevalence, severity and age-at-onset of many diseases. Sexual dimorphism is also seen in human autosomal gene expression, and has largely been explored by examining the contribution of genotype-by-sex interactions to variation in gene expression.ResultsIn this study, we use data from a mixture of pedigree and unrelated individuals with verified European ancestry to investigate the sex-specific genetic architecture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Many studies have aimed to identify sex-specific genetic control of autosomal gene expression (21)(22)(23)(24), however the evidence for differential genetic control of gene expression across the sexes is largely inconsistent. Indeed, our previous work has shown that, on average, males and females share a common autosomal genetic control of gene expression in whole blood (25). This is consistent with sex-differences in gene expression being due to differences in the regulatory genome across the sexes (10,11), and may be due to differential binding of sex hormones affecting the expression of nearby genes.…”
Section: Introductionsupporting
confidence: 68%
“…Many studies have aimed to identify sex-specific genetic control of autosomal gene expression (21)(22)(23)(24), however the evidence for differential genetic control of gene expression across the sexes is largely inconsistent. Indeed, our previous work has shown that, on average, males and females share a common autosomal genetic control of gene expression in whole blood (25). This is consistent with sex-differences in gene expression being due to differences in the regulatory genome across the sexes (10,11), and may be due to differential binding of sex hormones affecting the expression of nearby genes.…”
Section: Introductionsupporting
confidence: 68%
“…Kassam et al . examined the sex-specific genetic architecture of autosomal gene expression in whole blood samples from about one thousand men and one thousand women using DNA arrays [ 55 ]. No differences between men and women were found in autosomal genetic control of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between the sexes in complex traits could be partially explained by sex-specific gene expression regulation, which could lead to differences downstream across biological pathways and traits, and thus to the detection of GxS interactions in GWASs. Although studies have been carried out searching for differential gene expression between the sexes (sex-DE) in a variety of tissues of interest, studies linking sex to differences in gene expression regulation (sex-specific or sex-biased eQTLs) are few, with often contradictory results 5,[37][38][39][40] . These mixed results could be due to the contribution of GxS to gene expression being tissue specific, a lack of sufficient statistical power, or the fact that this contribution occurs only on a small number of genes .…”
Section: Sex Differences In Gene Expression Regulationmentioning
confidence: 99%